Acute and endothelial-specific Robo4 deletion affect hematopoietic stem cell trafficking independent of VCAM1. - Stephanie Smith-Berdan (Public Library of Science (PLoS), 2021)
Hematopoietic stem cell (HSC) trafficking is regulated by a number of complex mechanisms. Among them are the transmembrane protein Robo4 and the vascular cell adhesion molecule, VCAM1. Endothelial VCAM1 is a well-known regulator of hematopoietic cell trafficking, and our previous studies revealed that germline deletion of Robo4 led to impaired HSC trafficking, with an increase in vascular endothelial cell (VEC) numbers and downregulation of VCAM1 protein on sinusoidal VECs. Here, we utilized two Robo4 conditional deletion models in parallel with Robo4 germline knockout mice (R4KO) to evaluate the effects of acute and endothelial cell-specific Robo4 deletion on HSC trafficking. Strikingly similar to the R4KO, the acute deletion of Robo4 resulted in altered HSC distribution between the bone marrow and blood compartments, despite normal numbers of VECs and wild-type levels of VCAM1 cell surface protein on sinusoidal VECs. Additionally, consistent with the R4KO mice, acute loss of Robo4 in the host perturbed long-term engraftment of donor wild-type HSCs and improved HSC mobilization to the peripheral blood. These data demonstrate the significant role that endothelial Robo4 plays in directional HSC trafficking, independent of alterations in VEC numbers and VCAM1 expression.